Some Considerations on Abuse of Dominant Position - Ovidiu Maican (Romanian Journal of European Affairs, 2007)
Article 82 (formerly 86) EC contains four essential elements (an undertaking, a dominant position, an abuse of that position and the abuse must affect trade between member states). The term undertakings is subject to the same broad interpretation as that applied to article 81 (formerly 85) EC and covers the same activities, both public and private. The Community interest must be also taken into account. Although it is not clear precisely what this element of article 86 requires, it will clearly curtail the scope of the exception provided under this article. Although abusive behavior of undertakings in a dominant position is prohibited, it must be recalled that merely being in a strong position is not a problem in itself. It is necessary for major players in a market to be aware of their position because practices which would not fall foul of article 82 (formerly 86) EC, where an undertaking is not dominant, will do so where dominance is established. A refusal to deal by a non-dominant undertaking would not be an abuse within article 82 (formerly 86) EC, but it will be so where the undertaking is dominant.